EVALUATING THE IMPACT OF MECHANICAL COMPETENCY DEVELOPMENT ON CERTIFICATION ON WORK PERFORMANCE AT PT. XYZ - Rahmat Riyadi; Gembong Baskoro; rer. nat. Filiana Santoso (ILTEK : Jurnal Teknologi, 2026)
This study investigates the impact of mechanical competency development through training and certification on the performance of mechanics at PT XYZ, a nationwide heavy equipment distributor. The main issue lies in the high failure rate of certification exams, particularly in theory, caused by a misalignment between training materials and exam requirements. This mismatch reduces certification success rates, prolongs job completion times (lead time), and increases operational costs. Adopting a quantitative research design, the study utilizes surveys, SAP system data, and multiple regression analysis to examine the relationships among training, certification, work experience, and performance. Findings reveal that certification exerts a stronger influence than training alone, particularly in reducing lead time. Certified mechanics work faster, more accurately, and more efficiently. Moreover, work experience and task repetition significantly enhance performance. Therefore, an effective mechanic development strategy should integrate structured training, certification, and hands-on exposure to improve competency, lower costs, and boost productivity and customer satisfaction.